Islamic literacy as a preventive effort against domestic violence: Analysis of the meaning of wadhribuhunna in An-Nisa' verse 34 - Thamrin, Thamrin; Ismail, Hidayatullah (Priviet Social Sciences Journal, 2026)
Cases of Domestic Violence (KDRT) against women have increased significantly, both physically and psychologically. In this context, Surah An-Nisa' verse 34 provides gradual guidelines for dealing with nusyuz, including moral warnings that are often translated literally as "pukullah" (wadhribuhunna). This study aims to analyze the meaning of wadhribuhunna through a review of classical to contemporary scholars, sort out the meaning based on the rules of fiqh choosing a lighter mudharat, and apply it in modern household life with a theoretical approach of Symbolic Interaction. The results of the analysis show that the most strict mufasir groups, such as Al-Biqa'i, Wahbah al-Zuhaili, Hamka, Rashid Riḍā, and M. Quraish Shihab, emphasize symbolic and educational understanding of the word "hit", so that the risk of physical and psychological harm can be minimized. The application of this symbolic meaning is in harmony with the principle of benefit, encourages healthy communication, and strengthens household harmony. The Symbolic Interactionism approach emphasizes that the meaning of the verse is formed through social interaction, individual reflection, and negotiation of moral values, so that symbolic interpretation becomes an effective preventive strategy against domestic violence.